Corrigendum: Antimicrobial and antitubercular activity of novel pyrazole-4-carboxamide derivatives: Synthesis and characterization (Journal of Applied Pharmaceutical Science, 2023)
This corrigendum corrects the following article;Asha Deepthi C, Prathyusha J. Antimicrobial and antitubercular activity of novel pyrazole-4-carboxamide derivatives: Synthesis and characterization. J Appl Pharm Sci, 2023; 13(05):073–080. https://doi.org/10.7324/JAPS.2023.119430In the abovementioned article, the authors mistakenly submitted the article with the wrong sequence of authors. The article was submitted with the author sequence as C. Asha Deepthi, J. Prathyusha, and the same sequence was published in the Journal. Furthermore, the first name of the author ‘C. Asha Deepthi’ is misspelled. It should be read as ‘C. Asha Deepti’. The correct names and the sequence of the authors are J. Prathyusha, and C. Asha Deepti. Where J. Prathyusha is the first author of the article and C. Asha Deepti is the second and the corresponding author. This corrigendum corrects all the previous versions of the above article.